Ecchymoses and bruising – first diagnostic steps - Sułek, Kazimierz (Lekarz POZ, 2018)
Ecchymoses and bruising are frequently-encountered symptoms in the everyday outpatient practice of general practitioners. This article presents teh classification of vascular and platelets haemorrhagic diathesis because these two elements are the most frequent causes of such symptoms. The initial steps of diagnostics should cover anamnesis concerning circumstances of the appearance of skin changes, settlement of potential aetiology, and consideration of the inborn character in children. Physical examination, as well as visual assessment of skin and mucosal tissues, should exclude diseases of other organs. Laboratory investigations should also include a blood coagulation test because coagulation diathesis can also manifest with bruising.